Nutritional status and dietary habits in older adults with fixed implant dental prostheses: a case-control study - Homsi, George; Trulsson, Mats; Grigoriadis, Anastasios; Kumar, Abhishek (Frontiers in Nutrition, 2024)
Aim To evaluate the nutritional status, nutritional risk, and dietary habits of patients treated with bimaxillary implant-supported fixed prostheses in comparison with a group of natural dentate patients. Methods A study group (n = 25, 8 women, mean age = 70.6 ± 7.5 years) with bimaxillary implant-supported fixed prostheses and a control group (n = 25, 13 women, mean age = 69.0 ± 5.3) with a mean of 27.7 ± 1.8 natural teeth were recruited. The nutritional status and nutritional risk of the participants were evaluated with Mini Nutritional Assessment (MNA) and Seniors in the Community: Risk Evaluation for Eating and Nutrition; (SCREEN-14), while the dietary habits were recorded by data from a three-day dietary record. The data were analyzed with the Mann–Whitney U-test and independent t-test to evaluate the differences between the groups. Results The results showed that although both the groups had normal nutrition status as revealed by the MNA scores the study group showed significantly higher BMI (p = 0.005) but lower SCREEN-14 (p = 0.012) scores, than the control group. The results also showed that higher SCREEN-14 scores were significantly associated with higher odds of being in the control group, with an odds ratio of 1.159 (p = 0.024). Further, the results of the analysis of the dietary records showed that the participants in the study group consumed fewer meals (p = 0.006) and fewer varieties of food (p < 0.001), particularly fewer fruits (p = 0.011) than the control group. Conclusion The results indicate that people with fixed implant prostheses may be susceptible to nutritional deficiencies according to the SCREEN-14 scores compared to their natural dentate counterparts. Further, people with implant prostheses also tend to have higher BMI and consume a smaller variety of foods, especially fruits, than the natural dentate control group.